Respuesta :
Answer:
see explanation
Step-by-step explanation:
Calculate both AB and BC using the distance formula
d = √ (x₂ - x₁ )² + (y₂ - y₁ )²
with (x₁, y₁ ) = A(1, 1) and (x₂, y₂ ) = B(3, 6)
AB = [tex]\sqrt{(3-1)^2+(6-1)^2}[/tex]
= [tex]\sqrt{2^2+5^2}[/tex]
= [tex]\sqrt{4+25}[/tex] = [tex]\sqrt{29}[/tex]
Repeat the process with
(x₁, y₁ ) = B(3, 6) and (x₂, y₂ ) = C(5, 1)
BC = [tex]\sqrt{(5-3)^2+(1-6)^2}[/tex]
= [tex]\sqrt{2^2+(-5)^2}[/tex]
= [tex]\sqrt{4+25}[/tex] = [tex]\sqrt{29}[/tex]
Thus |AB | = |BC | = [tex]\sqrt{29}[/tex]
Answer:
explained
Step-by-step explanation:
Calculate both AB and BC using the distance formula
d = √ (x₂ - x₁ )² + (y₂ - y₁ )²
with (x₁, y₁ ) = A(1, 1) and (x₂, y₂ ) = B(3, 6)
AB =
=
= =
Repeat the process with
(x₁, y₁ ) = B(3, 6) and (x₂, y₂ ) = C(5, 1)
BC =
=
= =
Thus |AB | = |BC | =